The Determinants of Financial Distress of Basic Industry and Chemical Companies Listed in Indonesia Stock Exchange - Nurhayati, Nurhayati; Mufidah, Anna; Kholidah, Asna Nur (Review of Management and Entrepreneurship, 2018)
Understanding the factors that determine financial distress would help management prepare anticipating actions and anticipate the worst possible situation in the future. This study examines four fundamental factors of companies in the basic industry and chemical sectors listed at the Indonesian stock exchange. Nineteen companies were classified as financially distressed and thirty-three non-financially as distressed companies. The logistic regression test revealed debts to assets ratio (positive), current ratio (negative), and return on assets (negative) became predictors for possible financial distress. Total assets turn over did were not able to predict whether the companies belonged to financially distressed or non-financially distressed.